Liberalisation and deregulation in urban housing markets - Whitehead, Christine (Estudios de Economía, 2016)
The paper examines the attributes of housing that makes is difficult to provide it effectively in freely operating markets as well as the attributes which make administrative allocation problematic. It then goes on to discuss why the policy emphasis in many countries has moved towards liberalization to generate efficiency, while at the same time targeting assistance more directly towards lower income households. The paper discusses experience in a range of developed and developing countries, concentrating on the removal of administrative constraints on supply, particularly with respect to land, planning and the provision of infrastructure.